Formation and simulation of network aggregation behaviour. (30th October 2020) - Chen, Xiaohong; Chen, Ruohan
Network aggregation behaviour appears more and more frequently with the development of internet. In the virtual world, the speed and degree of network aggregation are much faster than those in the real world. In this paper, Monte Carlo simulation method is used for modelling and analysing network aggregation behaviour, to discuss the influence of different influence parameters on aggregation behaviour, and verify the rationality and effectiveness of the model through empirical analysis. The simulation results show that the speed of gathering is determined by the degree of influence of followers. In addition, the larger initial number is, the slower the aggregation will be.